(untitled) (Fiep Bulletin - online, 2013)
This study deals with a literature research that aimed to identify the sentiments that permeate the daily lives of mothers during the diagnosis and treatment of their children with cancer. The childhood cancer affects more than five thousand children and adolescents in our country, leading to more than two thousand deaths a year in the ages of 0 to 19 years, with a gradual increase in cases. Mothers, in most cases, accompanying the children since the early signs and symptoms through the anguish of the confirmation of diagnosis and throughout the treatment of the disease and are often dealing with the physical and emotional exhaustion. The data of the study were obtained by searching the databases of USP, UNICAP, LILACS and SciELO, during the months of March and April 2008. The articles were selected and grouped into four categories: 1) the gaze of mothers before the diagnosis of cancer, 2) feelings of the mothers experienced during treatment, 3) feelings of the mothers after treatment, 4) theory of social representations inserted in that context . It follows that having a child with cancer is always live surrounded by feelings of: fear, sadness, uncertainty, anxiety, among others. There is a need of, by the professionals engaged in this area, conducting a full assistance to support these mothers along all this history, looking for these mothers to provide a better understanding of its holdings in that context.